Osseointegrated implant associated with guided bone regeneration: a case report (Research, Society and Development, 2022)
Implantology has been used on rehabilitation of edentulous patients, however, some clinical situations, such as bone atrophy, may limit treatments with osseointegrated implants (OI). However, the technological advance of the biomaterials and the development of bone regeneration techniques made it possible. The present article is about a patient who had the region of the dental elements 21 and 22 edentulous and with severe horizontal bone atrophy. Guided Bone Regeneration (GBR) was performed with a biocompatible biphasic calcium phosphate alloplastic material, and simultaneous placement of narrow OI. After 4 months postoperatively, the GBR and the installation of the OI were considered clinically and imagenologically satisfactory.GBR is an applicable procedure that can be used in regions with horizontal and vertical alveolar bone atrophy. In the clinical case studied, it was possible to verify that the GBR technique associated with an alloplastic biomaterial allowed an improvement in the thickness of the hard tissue in the region and, also, allowed the installation of narrow IO simultaneously.